Versatility of unsaturated polyesters from electrospun macrolactones: RGD immobilization to increase cell attachment. Issue 2 (28th July 2021) - de Oliveira, Fernando Cabral Sales; do Amaral, Ronaldo Jose Farias Correa; dos Santos, Luiza Erthal Cardoso; Cummins, Cian; Morris, Michael M.; Kearney, Cathal J.; Heise, Andreas
Abstract: Poly(globalide) (PGl), an aliphatic polyester derived from unsaturated macrocylic lactone, can be cross‐linked during electrospinning and drug‐loaded for regenerative medicine applications. However, it lacks intrinsic recognition sites for cell adhesion and proliferation. In order to improve their cell adhesiveness, and therefore their therapeutic potential, we aimed to functionalize electrospun PGl fibers with RGD sequence generating a biomimetic scaffold. First, an amine compound was attached to the surface double bonds of the PGl fibers. Subsequently, the amino groups were coupled with RGD sequences. X‐ray photoelectron spectroscopy (XPS) analysis confirmed the functionalization. The obtained fibers were more hydrophilic, as observed by contact angle analysis, and presented smaller Young's modulus, although similar tensile strength compared with non‐functionalized cross‐linked fibers. In addition, the functionalization process did not significantly alter fibers morphology, as observed by scanning electron microscopy (SEM). Finally, in vitro analysis evidenced the increase in human mesenchymal stromal cells (hMSC) adhesion (9.88 times higher DNA content after 1 day of culture) and proliferation (3.57 times higher DNA content after 8 days of culture) compared with non‐functionalized non‐cross‐linked fibers. This is the first report demonstrating the functionalization of PGl fibers with RGD sequence, improving PGl therapeutic potential and further corroborating the use of this highly versatile material toward regenerative medicine applications.